Genomic Analysis of Sexual Dimorphism of Gene Expression in the Mouse Adrenal Gland - El Wakil, A.; Mari, B.; Barhanin, J.; Lalli, E. (Hormone and Metabolic Research, 2013)
A relevant gender difference exists in adrenal physiology and propensity to disease. In mice, a remarkable sexual dimorphism is present in several components of the hypothalamic-pituitary-adrenal axis, with females displaying higher adrenal weight, plasma ACTH, corticosterone, and aldosterone levels than males. The molecular bases of this sexual dimorphism are little known. We have compared global gene expression profiles in males vs. female mouse adrenal glands and also studied the effect that testosterone treatment and castration have on adrenal gene expression in female vs. male mice, respectively. Our study evidenced a set of 71 genes that are coordinately modulated according to sex and hormonal treatments and represent the core sexually dimorphic expression program in the mouse adrenal gland. Moreover, we show that some genes involved in steroid metabolism have a remarkable sexual dimorphic expression and identify new potential markers for the adrenal X-zone, a transitory cellular layer in the inner adrenal cortex, which spontaneously regresses at puberty in males and during the first pregnancy in females and has an uncertain physiological role. Finally, sexually dimorphic expression of the transcriptional regulators Nr5a1 and Nr0b1 may explain at least in part the differences in adrenal steroidogenesis between sexes.
Keywords: gene expression; adrenal gland; genomics